Pengaruh Pembiayaan Mudharabah, Pembiayaan Musyarakah, dan Piutang Murabahah Terhadap Return on Assets (Roa) Pada Bank Syariah (PT. Bank Bni Syariah) Periode 2016 – 2020 - Purisma Fathnia Rizqi; Isro’iyatul Mubarokah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Financing is implemented to make it easier for customers in Islamic banks. With the existence of various types of financing, it can certainly affect the level of profitability to assess the company's profitability. Based on the data that has been obtained, Bank BNI Syariah has a level of profitability in the form of a fluctuating ROA per quarter starting from 2016-2020. Therefore, the purpose of this study is to see whether or not there is an influence of the relationship between mudharabah financing, musyarakah financing, and murabahah receivables on ROA (Return on Assets) at Bank BNI Syariah in 2016 – 2020. The position of the financial statements (balance sheet) in Bank BNI Syariah for the period 2016 – 2020 is used as the population while taking samples using a saturated sample technique. The data used is secondary data taken through the OJK website in 2016-2020. To test this research, SPSS Version 25 software was used. Data processing began with the classic assumption test and then continued with the T test and also the F test. The results showed that mudharabah financing and murabahah collection did have an effect on ROA at Bank BNI Syariah. Meanwhile, for musyarakah financing, there is no effect on ROA at Bank BNI Syariah